Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's solve the problem step-by-step.
Given:
1. [tex]\( a + b + c = 5 \)[/tex]
2. [tex]\( ab + bc + ca = 10 \)[/tex]
We want to find [tex]\( a^3 + b^3 + c^3 - 3abc \)[/tex].
To approach this problem, we use a known algebraic identity:
[tex]\[ a^3 + b^3 + c^3 - 3abc = (a + b + c)\left((a + b + c)^2 - 3(ab + bc + ca)\right) \][/tex]
Plugging in the given expressions for [tex]\( a + b + c \)[/tex] and [tex]\( ab + bc + ca \)[/tex], we can simplify this identity.
First, let's calculate:
[tex]\[ (a + b + c)^2 = 5^2 = 25 \][/tex]
Next:
[tex]\[ 3(ab + bc + ca) = 3 \times 10 = 30 \][/tex]
Now, substitute these values into our identity:
[tex]\[ a^3 + b^3 + c^3 - 3abc = (5)\left(25 - 30\right) \][/tex]
Simplify inside the parentheses:
[tex]\[ 25 - 30 = -5 \][/tex]
Thus, we have:
[tex]\[ a^3 + b^3 + c^3 - 3abc = 5 \times (-5) = -25 \][/tex]
So, we have shown that given [tex]\( a + b + c = 5 \)[/tex] and [tex]\( ab + bc + ca = 10 \)[/tex], it follows that:
[tex]\[ a^3 + b^3 + c^3 - 3abc = -25 \][/tex]
Therefore, the proof is complete.
Given:
1. [tex]\( a + b + c = 5 \)[/tex]
2. [tex]\( ab + bc + ca = 10 \)[/tex]
We want to find [tex]\( a^3 + b^3 + c^3 - 3abc \)[/tex].
To approach this problem, we use a known algebraic identity:
[tex]\[ a^3 + b^3 + c^3 - 3abc = (a + b + c)\left((a + b + c)^2 - 3(ab + bc + ca)\right) \][/tex]
Plugging in the given expressions for [tex]\( a + b + c \)[/tex] and [tex]\( ab + bc + ca \)[/tex], we can simplify this identity.
First, let's calculate:
[tex]\[ (a + b + c)^2 = 5^2 = 25 \][/tex]
Next:
[tex]\[ 3(ab + bc + ca) = 3 \times 10 = 30 \][/tex]
Now, substitute these values into our identity:
[tex]\[ a^3 + b^3 + c^3 - 3abc = (5)\left(25 - 30\right) \][/tex]
Simplify inside the parentheses:
[tex]\[ 25 - 30 = -5 \][/tex]
Thus, we have:
[tex]\[ a^3 + b^3 + c^3 - 3abc = 5 \times (-5) = -25 \][/tex]
So, we have shown that given [tex]\( a + b + c = 5 \)[/tex] and [tex]\( ab + bc + ca = 10 \)[/tex], it follows that:
[tex]\[ a^3 + b^3 + c^3 - 3abc = -25 \][/tex]
Therefore, the proof is complete.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.